Perancangan UI/UX Aplikasi Food & Beverage Mobile Berbasis User Centered Design - Zakky Rabbani; Kurniawan Dwi Irianto (Journal of Information System Research (JOSH), 2025)
The Food & Beverage (F&B) industry in Indonesia is growing rapidly, yet many mobile applications still fail to deliver an optimal user experience (UX) due to unintuitive user interface (UI) designs, inefficient ordering systems, and lack of integrated payment methods. These issues negatively impact user satisfaction and application usability. This study aims to design the user interface (UI) and user experience (UX) of a mobile food & beverage application that meets user needs, accommodates industry expectations, and is evaluated for effectiveness using the User-Centered Design (UCD) approach. The research employed the UCD methodology, involving user interviews, persona development, wireframing, prototyping, and usability testing. The evaluation was conducted using the System Usability Scale (SUS) with 15 respondents. The results show that the prototype of the “KuliNow” application achieved an average SUS score of 84, categorized as “Excellent.” Key features include integrated mobile banking payments, direct communication with restaurants, social media integration, pre-order functionality, efficient order management, and a reliable review and rating system. This study demonstrates that the UCD approach is effective in developing intuitive, user-focused mobile applications.